Study on Removal of Heavy Metal Ni Pollution by Microbial Mineralization Consolidation. (December 2018) - Sui, Ming; Wang, Jingxia; Zhang, Chongjun; Tang, Xianhua; Yue, Wenxi; Zhu, Keyong
Abstract: In this study, a strain of Pichia pastoris strain N was screened from the soil around the local electroplating plant. This carbonate mineralization bacteria produced urease during the growth and metabolism process, decomposing the substrate urea and producing ammonia ions. And carbonate ions, mineralized to consolidate the heavy metal Ni in the soil. The basic physiological and biochemical properties, growth curve, urease activity and influencing factors of strain N and mineralization analysis experiments were analyzed. The conclusions of this experiment can provide a theoretical basis for the removal of heavy metals from soil in the field and can improve the application value of this technology.